Evaluation of national programme for prevention and control of cancer, diabetes, cardiovascular diseases, and stroke (NPCDCS) in north coastal Andhra Pradesh a mixed method study - R.M.Jahnavi Sampathi Rao; K.V.Phani Madhavi; V.Haritha; Devi Madhavi Bhimarasetty (Global Journal of Medicine and Public Health, 2024)
Introduction Program Monitoring and Evaluation (M & E) are important components of any program and are critical to sound strategic planning. NCDs are the leading causes of Morbidity and mortality. The present study was undertaken to assess the implementation of the NPCDCS programme and to explore the perception of community availing the services.